Review on Sphaeranthus indicus Linn. (Kot.t.aikkarantai) - Ramachandran, Shakila (Pharmacognosy Reviews)
Sphaeranthus indicus Linn. is from the aroma family Asteraceae. It is also known with other synonyms such as Munditika, Mundi, Shravana, Bhikshu, Tapodhana, Mahashravani, Shravanahva, Shravanashirshaka. It is abundantly distributed in damp areas in plains and also as a weed in the rice fields. In the Indian system of medicine, the plant as a whole plant or its different anatomical parts viz., leaf, stem, bark, root, flower and seed are widely used for curing many diseases. The plant is bitter, stomachic, restorative, alterative, pectoral, demulcent and externally soothing. The whole plant and its anatomical parts have been reported with different types of secondary metabolites which include eudesmanolides, sesquiterpenoids, sesquiterpene lactones, sesquiterpene acids, flavone glycosides, flavonoid C‑glycosides, isoflavone glycoside, sterols, sterol glycoside, alkaloid, peptide alkaloids, amino acids and sugars. The essential oils obtained from the flowers and whole plants were analyzed by different authors and reported the presence of many monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons and oxygenated sesquiterpenes. The whole plants, its isolated secondary metabolites and different anatomical parts have been reported for ovicidal, antifeedant, anthelmintic, antimicrobial, antiviral, macrofilaricidal, larvicidal, analgesic, antipyretic, hepatoprotective, antitussive, wound healing, bronchodilatory, mast cell stabilizing activity, anxiolytic, neuroleptic, immunomodulatory, anti‑diabetic, antihyperlipidemic and antioxidant, antioxidant, central nervous system depressant, anti‑arthritic, nephroprotective, anticonvulsant activities and many other activities. It is also effective on psoriasis. In the present paper, the plant is reviewed for its phytochemical and pharmacological reports in detail.
Keywords: 5; 4’‑Dimethoxy‑3’‑prenylbiochanin‑7‑O‑β‑D‑galactoside; 7‑hydroxy eudesmanolide; Kot· t · aikkarantai; Munditika churna; Veezhi Ennai